A Study of Environmentally-Sound Geotourism Potential in Sumedang Regency - Novarlia, Irena (International Journal Labs, 2023)
Background: Geotourism is a type of sustainable and conservation-based tourism that can provide educational value for the community on the importance of preserving nature. Aim: The research was carried out with a field survey to determine the potential of Cipadayungan waterfall in Padasari Village, Cimalaka District, Sumedang Regency in the opportunity to develop geotourism. Method: The research method used is descriptive qualitative with survey analysis which refers to classification according to feasibility indicators and quantitative descriptive based on the evaluation of geotourism potential in terms of environmental aspects. Findings: The results of the study prove the potential of Cipadayungan waterfall to be included in the category of having decent potential as an educational geotourism destination. The biggest hope is that the geotourism of Cipadayungan waterfall can be more developed and popular as an environmentally friendly geotourism destination in Indonesia.